Oral Health Knowledge and Behavior in Relation to Oral Hygiene and Gingival Condition among a Group of Industry Workers - Abdulla, Muna (Journal of Baghdad College of Dentistry, 2018)
Background: In Iraqi communities, the workers considered the largest population groups, so increasing their dental education by increasing the care for their dental health knowledge and behavior is very important, the present study was aimed to evaluate the gingival health and oral hygiene in relation to knowledge and behavior among a group of a workers selected randomly from Al Fedaa company in Baghdad city. Materials and methods: A sample of 110 workers (65 men and 45 women) included in this study, a questionnaire used to evaluate their oral health knowledge and behavior. The gingival health condition of the workers was examined by using Loe and Silness index (1963), Silness and Loe index (1964) was used to asses plaque quantity, and Ramfjord index (1959) used to asses calculus quantity, SPSS version 18 was used to analyze the data of the study statistically. Results: This study showed that no significant differences between plaque, calculus, and gingival index with the education degree of the workers. About the knowledge the result showed no significant differences in questions asking about type and characteristic of dental caries, best type of tooth paste, brushing technique. There is a significant differences found in questions regarding gingival health and bleeding. The behavior of the workers showed no significant differences in questions regarding quantity of brushing teeth, using assistant aid, better time for eating sweet, while there is a significant difference in question about smoking and gingival health and duration of brushing time. Conclusion: Increasing the dental education by using the help of social media, schools, and national educational programs will improve the dental knowledge and behavior which affect positively on the oral hygiene